The Influence of Organizational Culture, Transformational Leadership and Well-Being in the Workplace on Work Involvement of Private University Lecturers in South Jakarta - Ade Pifianti; Rugaiyah Rugaiyah; Thamrin Abdullah (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aims to examine the effect of organizational culture, transformational leadership and well-being in the workplace on lecturers' work engagement, at 290 private university lecturers in South Jakarta. The research method used a survey method. The instruments used a questionnaire as material for group discussion forums (FGD). Furthermore, data analysis used Path Analysis. The results of this study indicated that the influence of organizational culture (X1), transformational leadership (X2), well-being at work (X3) on lecturer involvement (Y), with the seven hypotheses proposed showing the result that the coefficient of determination was 0.367. This states the variation of changes in quality improvement that occurs in the variables X1, X2 and X3 can explain 0.367 variations in the decrease in the Y variable. The influence of other variables that affect the work involvement of lecturers is 0.633. In addition to the three variables, other variables affect the work involvement of lecturers, with a significant effect of 0.633. In this study, the impact is obtained that the involvement of lecturers is influenced by various internal and external aspects of lecturers, so that the interaction of leadership, welfare and institutional climate is needed.